The Call for the Abolition of Mental Health Law: The Challenges of Suicide, Accidental Death and the Equal Enjoyment of the Right to Life. (27th November 2018) - Wilson, Kay
ABSTRACT: Mental health law provides for the involuntary detention and psychiatric treatment of persons with severe mental impairment. While it has always been controversial, since the entry into force of the Convention on the Rights of Persons with Disabilities (CRPD), certain scholars, disability and human rights advocates and international human rights bodies have called for the abolition of mental health law on the grounds that it is discriminatory and is an unnecessary interference with individual liberty and bodily integrity. A number of alternative approaches that use the provision of decision-making support to decrease coercion and increase the recognition of the subjective 'will' and 'preferences' of persons with mental impairment have also emerged. However, throughout the debate on the future of mental health law, the right to life has received little attention. This article explores the contours of the right to life contained in Article 10 of the CRPD in the context of the debate surrounding the future of mental health law with a focus on the challenges of suicide and avoidable accidental death.